Pengaruh Pupuk Gandasil D Terhadap Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogaea L.) - Deni Soviani; Adrianus Adrianus; Abdullah Sarijan (Musamus Journal of Agrotechnology Research, 2019)
This study aims to determine the effect of Gandasil D fertilizer on growth and the production of peanut (Arachis hypogaea L.). The research was carried out in Kuprik, District Semangga, start from July until October 2012. The experimental design used was randomized block design with 4 (four) treatment and three replication. The treatment was Gandasil D fertilizer: 1,0 g/l, 1,5 g/l, 2,0 g/l and without Gandasil D fertilizer (control). The results showed that the treatment of Gandasil D fertilizer not showing significant effect on the growth and the production of peanut. But the treatment of D2 (Gandasil D) with dosis 1,5 g/l can increase the production a peanut higher than another treatment, the result is 1,40 kg/plot or 2,91 ton/ha.